Tracing Dalcroze-Inspired Practices in Finland : Three Artist-Pedagogues at the Sibelius Academy in the Twentieth Century - Juntunen, Marja-Leena (Boydell & Brewer, 2025)
In this chapter I discuss three Finnish artists-pedagogues and examine how they applied the ideas of Émile Jaques-Dalcroze in their work at the music institution that was first called the Helsinki Music Institute (founded in 1882), then the Helsinki Conservatory (1924), and finally Sibelius Academy (1939–, later referred to as SibA in the text) – nowadays the only university-level music institution in Finland. These artists are Maggie Gripenberg, a student of Jaques-Dalcroze, Ilta Leiviskä, a student of Gripenberg, and Inkeri Simola-Isaksson, a student of Leiviskä. --
Keywords: Dalcroze-rytmiikka; pedagogiikka; musiikkikasvatus